3D numerical simulation of GMAW Cold Metal Transfer using response surface methodology. (April 2022) - Escribano-García, R.; Rodriguez, N.; Zubiri, O.; Piccini, J.; Setien, I.
Abstract: This work presents a fast methodology to adjust heat source model parameters that reproduce the evolution of temperatures and distortions of a welded joint. This joint is obtained by the Cold Metal Transfer (CMT) process, a variant of the most frequently used gas-shielded metal arc welding (GMAW) process. The proposed methodology combines Response Surface Method (RSM) and Finite Element Method (FEM). The thermal simulation is tackled by a 3D transient FEM-model with a Goldak heat flux; and the mechanical behaviour is addressed by a 3D elastic-plastic FEM-model. A Design of Experiments (DoE) is applied to simulate a set of thermal and mechanical FEM-models varying the heat source parameters. Then, the temperatures and distortions of all simulations are gathered and used to build polynomial regression models that are able to predict temperatures and distortions as functions of the heat flux parameters. Finally, best parameters are found using RSM. The method is based on automation of pre and post processes that replaces the trial and error process, which involves large amount of engineering time. Highlights: 3D FEM-model of GMAW - Cold Metal Transfer process Optimal heat flux dimensions by Response Surface Method Good correlation between the measured and simulated temperatures and distortions Fast and reliable fitting process